1995
DOI: 10.1007/bf00188460
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of congenital diaphragmatic hernia in a 6-month-old child

Abstract: This report describes the laparoscopic approach of closure of a congenital left posterolateral diaphragmatic hernia in a 6-month-old boy. The pros and cons of such an approach are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…The first report of laparoscopic diaphragmatic hernia repair was in 1995 on a 6-month-old-infant [29]. Since then, this procedure has been performed by both the laparoscopic and thoracoscopic routes [30].…”
Section: Discussionmentioning
confidence: 99%
“…The first report of laparoscopic diaphragmatic hernia repair was in 1995 on a 6-month-old-infant [29]. Since then, this procedure has been performed by both the laparoscopic and thoracoscopic routes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we could use laparoscopy for CDH as proposed in the first published minimally invasive CDH repair [3][4][5][6]. In laparoscopy we start with an empty abdomen and good sight of the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly the first endoscopic repair of a late-presenting diaphragmatic hernia in a child was performed by laparoscopy in 1995 van der Zee [3] and later by other groups [4][5][6], but in 2001 the thoracic access for children was revived by Becmeur [7] who reported thoracoscopic closure of three late-presenting diaphragmatic hernias in toddlers but not in neonates [8]. We report a low-pressure thoracoscopic repair of a congenital diaphragmatic hernia in a resuscitated, ventilated neonate.…”
mentioning
confidence: 99%
“…Advance in minimally invasive surgery in children has allowed for application of laparoscopy and thoracoscopy in various neonatal conditions, including congenital diaphragmatic hernia. The first successful laparoscopic repair of congenital diaphragmatic hernia in an infant was reported by van der Zee et al in 1995 [4]. In the same year, Silen et al [5] reported the first successful thoracoscopic congenital diaphragmatic hernia repair.…”
Section: Introductionmentioning
confidence: 96%